2015
DOI: 10.3938/jkps.66.1649
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on Kubas-type hydrogen-storage nanomaterials: from theories to experiments

Abstract: Transition-metal (TM) atoms are known to form TM-H2 complexes, which are collectively called Kubas dihydrogen complexes. The TM-H2 complexes are formed through the hybridization of the TM d orbitals with the H2 σ and σ * orbitals. The adsorption energy of H2 molecules in the TM-H2 complexes is usually within the range of energy required for reversible H2 storage at room temperature and ambient pressure (−0.4 ∼ −0.2 eV/H2). Thus, TM-H2 complexes have been investigated as potential Kubas-type hydrogen-storage ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…This rule is for calculating the number of hydrogen in Kubas‐type storage. Generally, transition metals agglomerate due to their vast cohesive energy of around 4 eV, resulting in reducing hydrogen storage capacity [55a,56] . It is reported that calcium atoms can also form complexes with hydrogen molecules with lesser cluster forming capacity due to low cohesive energy (1.83 eV).…”
Section: Hydrogen Storage Mechanism In Solid‐state Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This rule is for calculating the number of hydrogen in Kubas‐type storage. Generally, transition metals agglomerate due to their vast cohesive energy of around 4 eV, resulting in reducing hydrogen storage capacity [55a,56] . It is reported that calcium atoms can also form complexes with hydrogen molecules with lesser cluster forming capacity due to low cohesive energy (1.83 eV).…”
Section: Hydrogen Storage Mechanism In Solid‐state Materialsmentioning
confidence: 99%
“…It is reported that calcium atoms can also form complexes with hydrogen molecules with lesser cluster forming capacity due to low cohesive energy (1.83 eV). Therefore, Ca atoms are considered an excellent option for hydrogen storage via Kubas interaction [55a] . Many experimental studies have been done based on theoretical predictions and found that Kubas‐type interactions are stronger than Van der Waals interactions but weaker than chemisorption bonds [55a] …”
Section: Hydrogen Storage Mechanism In Solid‐state Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In chemisorption, H 2 molecules dissociate into double H atoms and even migrate to the material forming chemical bonds, which are strong. 6 Kubas-type orbital interaction 13,14 is similar to physisorption, in which the H-H bond in an H 2 molecule is elongated but not broken. It improves the hydrogen adsorption energy of transition metals (TMs)decorated carbon composites (0.10-0.80 eV) 6 and makes most of the hydrogen gravimetric storage capacities satisfy the target of the U.S. Department of Energy ($6.5 wt%).…”
Section: Introductionmentioning
confidence: 97%
“…One area of inorganic chemistry where NMR spectroscopy has been especially useful is in the study of dihydrogen complexes, M­(H 2 ), in which an essentially intact dihydrogen ligand binds “side-on” to a metal center, indicated by a short H–H distance, as low as ∼0.85 Å. Dihydrogen complexes are fundamentally important because of this mode of binding, which makes them prototypical σ complexes . Dihydrogen complexes also play a significant role in catalysis and bond activation and can potentially act as hydrogen storage materials when integrated into nanostructures …”
mentioning
confidence: 99%